The Influence of Student Management Skills Training on Communication Effectiveness in Student Organizations. - Seneru, Wistina; Irawan, Dedi; Manggalani, Rina; Kasrah, Rini; Wibawa, Resdhi; Octavia, Kathina (LPPM STIAB JINARAKKHITA LAMPUNG, 2024)
In the 21st century era of globalization, students are faced with the challenge of becoming adaptive and competitive individuals. Student Management Skills Training (LKMM) plays an important role in equipping students with managerial skills and effective communication. This research uses a qualitative approach with a literature analysis design to explore the influence of LKMM on communication effectiveness in student organizations. The results showed that the training not only improved students' communication skills, but also strengthened their managerial and strategic decision-making skills. LKMM helps students understand the organizational structure, increases self-confidence, and encourages active involvement in the organization. Thus, LKMM contributes significantly to the effectiveness of student organizations, creating a more productive and collaborative environment.